Investigation into the Rockfall Hazard along Lengpui-Aizawl Highway, NH-44A, Mizoram, India - Verma A.K.; Sinha R.K.; Sardana S.; Jaswal M.; Singh T.N. (My University, 2025)
Rockfall is a critical problem in the hilly regions. The Lengpui-Aizawl highway has witnessed many rockfalls and other types of landslide events in the past few years. This highway is imperative to the area as it links the Lengpui airport with the city. Most of the rock slopes along this highway are prone to rockfall, thus requires proper investigation. In this study, an investigation into the rockfall hazard was carried out on the nine rock slopes using the rockfall hazard rating system (RHRS) approach along NH-44A. Based on an extensive field investigation, the analysis shows that two out of nine slopes are more hazardous than the others as the RHRS score for these slopes is higher than 500. Furthermore, rockfall simulations were performed for hazardous slope to quantify the risk in terms of bounce height, velocity, kinetic energy and maximum reach of falling rock blocks. The simulation result reveals that vehicles on the roadway are under continuous threat. The potential falling blocks have a kinetic energy of 196 kJ which is enough to damage the buildings, vehicles and fatalities. © 2021, Indian Geotechnical Society.